GO GREEN VS GO ECONOMY - Putri, Sukma Jenny Emadina; Hikam, Reza Maulana (Jurnal Politik Pemerintahan Dharma Praja, 2024)
Politics as a vital role in policy formulation has an influence on waste management in Indonesia. Ethical and normative violations regarding waste imports often occur. This is because there are gaps in legislative products and positive law in the same field. As stated in Law no. 18 of 2008 concerning Waste Processing shows that the import of waste is an activity that is prohibited in any form. However, there was an overlap in regulations, namely in Minister of Trade Regulation No. 30 of 2021 which notes that it is permissible to import waste for industrial activities except for Toxic and Hazardous Materials (B3). This writing aims to analyze various overlapping realities and possibilities regarding the implementation of these regulations. The political interest perspective also shows the dynamics of its formulation. It turns out that politicians tend to have different standing positions even though they are still in the same commission group. It cannot be denied that there is differentiation of views which are then grouped into camps based on several possible influences, namely variations in the background of politicians and interest groups or political parties. Therefore, it is classified in this research that the group that supports waste imports is Go Economy, and vice versa, those who reject waste imports are classified as Go Green. The meaning of this term shows a contradiction in attitudes and implementation which has resulted in a polemic during waste import regulations in Indonesia.